Konotacje tekstowe a pojęciowy model słowa (na przykładzie wyrazu bluszcz w poezji młodopolskiej) - Kuryłowicz, Beata (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2010)
The present sketch attempts to provide a semantic description of the word bluszcz [ivy] in “Young Poland” literary period in order to present and prove the importance and the place of the vast array of textual connotations in the conceptual model of the word. The concept of an open-ended definition and the principle of internal motivation have all made it possible to reveal the textual connotations of the word bluszcz within the scope of its different degree of establishment and precision. These are the features that, though weak and fleeting, still perform very important functions because they introduce order into the semantic structure of the word and bond it together. Each and every distinctive feature has a strictly defined place in the structure. To reveal these various semantic components would not be possible with the application of traditional methods of semantic analysis.